Trp-Trp acts as a multifunctional blocker for human bitter taste receptors, hTAS2R14, hTAS2R16, hTAS2R43, and hTAS2R46. Issue 6 (12th April 2021) - Ojiro, Ichie; Nishio, Hiromi; Yamazaki-Ito, Toyomi; Nakano, Shogo; Ito, Sohei; Toyohara, Yoshikazu; Hiramoto, Tadahiro; Terada, Yuko; Ito, Keisuke
ABSTRACT: Many functional food ingredients activate human bitter taste receptors (hTAS2Rs). In this study, A novel inhibitor, Trp-Trp, for hTAS2R14 was identified by searching for the agonist peptide's analogs. Trp-Trp also inhibited hTAS2R16, hTAS2R43, and hTAS2R46, which share the same agonists with hTAS2R14. The multifunctional characteristic of Trp-Trp is advantageous for use as bitterness-masking agents in functional foods.